IMF Committee on Balance of Payments Statistics : Annual Report 2006. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2006)
This report constitutes the annual report of the IMF Committee on Balance of Payments Statistics (Committee). The Committee, which held its annual meeting at the European Central Bank (ECB) in Frankfurt, Germany, in October 2006, was established in 1992 to improve the availability, consistency, and reliability of balance of payments and international investment position statistics worldwide. This annual report provides an overview of recent trends in balance of payments and international investment position statistics, discusses the Committee's work program during 2006, and reviews the issues the Committee plans to address in the coming year.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet